The Development of Technology and Information and Its Impact on Notarial Practice in Relation to Legal Certainty - Desintha, Pande Ketut Natalia; Khoirunnisa, Nabila; Vania, Elsya; Effendy, Edrick Edwardina (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
The development in the current digital era has certainly brought significant changes in various aspects of life, including in notary practice. Therefore, this journal discusses the impact of technology and information on notary practice, with a focus on the aspect of legal certainty related to the concept of Cyber Notary. While there are still concerns in the practical and ethical aspects of implementing Full Cyber Notary in Indonesia, thereforeThrough legal analysis and literature study, this journal highlightsvarious problems of implementing Cyber Notary in Indonesia based on ethical and practical aspects such as the non-accommodation of Cyber Notary in laws and regulations, especially the Notary Law and the unpreparedness of the Cyber Notary implementation system including human resources and uneven distribution of infrastructure. Therefore, the Author Team provides a solution mechanism, namely the Cyber Notary practice method that reconciles laws and regulations related to Notaries in Indonesia reviewed based on progressive law. The Author Team provides a resolution mechanism with the implementation of Cyber Notary in a hybrid manner, which is a combination of current notary practices, namely conventionally with digital implementation, this is as the concept of progressive law which states that there are always weaknesses in the dynamics of law, as we know that existing laws will certainly always change and develop in society along with the social dynamics that occur. In implementing this hybrid system, it is important to adjust the laws related to Cyber Notary to the work area, the person appearing and reading the deed, signing to storing the deed, in addition, related parties such as the Indonesian Notary Association (INI) are also needed in the training and certification process specifically for notaries who will carry out Cyber Notary. Because in the context of implementing Cyber Notary, it is necessary to adjust the laws and regulations in order to provide legal certainty for Notaries and ensure the legality and authentication of electronic deeds are equivalent to conventional deeds, so that there is no overlap or ambiguity related to Cyber Notary in the formation or storage of an authentic deed.